التناص القرآني في شعر النقائض الأموية Intertextuality Quranic in Umayyad opposites hair - Ahmed R.A Rawajbeh; Tengku Ghani Tengku Jusoh; Md.Nor Abdullah; Zulkarnain Mohamed (Universiti Kebangsaan Malaysia, 2012)
The poets of opposites poems take their knowledge from multi-springs of knowledge. So, the direction of Islamic values were added to the knowledge that take from the past and its literature, and from present Islam and its acquaintances, so the poetic culture was colored with the color of the culture which they take. It was the way for the best poets to serve their purpose and to deliver their messages. There is no doubt that the Quran was afar distance of both recipient and poet for his eloquence this type of poem has been associated with the name of obscenity because of the large number insults and exposure of the taboos. This article came to reveal the relationship between the poetic text and the Quranic text in the poem of the three Umayyad poets and to wipe the dust of obscenity which knighted him and to identify the impact of the holy Quran upon its simple, compound and inspiration system and address the extent of correlation of poetic text and overlap with the Holy Quran.